Recommendations for specimen collection for detection and diagnosis of COVID-19 - Dall'Agnol, Juliana (2021)
Introduction: The spread of SARS-CoV-2 has caused a global public health crisis (pandemic). One of the most important measures to control the transmission chain of the new coronavirus is to identify those infected through laboratory testing. Objective: Synthesize the recommendations for the specimen collection for detection and diagnosis of COVID-19. Methods: This is an integrative review, considering the publications of the following databases: PubMed and Google Academic from January 2020. Results: 468 publications were identified, 20 of which were considered eligible. The publications recommend that technical training for specimen collection and careful observation of infection prevention protocols are fundamental. This manuscript highlights the steps for specimen collection as materials for collection, storage, transportation, individual protection, and laboratory analysis of samples. Currently, the Reverse Transcription - Polymerase Chain Reaction test is the recommended and gold standard method of identifying COVID-19 cases. Serological tests play an important role in research and surveillance. Conclusion: In summary, the documents ensure that the RT-PCR is the gold standard for SARS-CoV-2 detection and recommend standardization of collection and conditioning methods to avoid errors related to the collection and false negative results.